Active pedagogy and ict in education in secondary school teacher training in francophone sub-saharan Africa , scope and limits : the case of the Republic of Congo - (:unkn) unknown (My University, 2023)
There are many speeches that accord importance to the integration of new pedagogies and new technologies in the search for quality and equitable education in sub-Saharan Africa. However, the difficulties that sub-Saharan African countries must overcome to integrate them into their education systems are colossal. These are mainly linked to five factors: political, economic, technological, human, and cultural situations. The last two factors interest us the most for our research, particularly resistance to change and lack of teacher training. Associated to the actions of the NGO Action Real, we experimented with a training program in ICT and in Active and Participatory Pedagogy with 100 participants (inspectors and teachers) in the Republic of Congo. We then evaluated the impact that this training programme had in the pedagogical practices of teachers and if it is able to generate a change despite the unfavorable structural conditions and if so, of what nature these changes are. Finally, we propose a training program that takes into account the elements collected on the field. We followed an intervention-research approach.
Keywords: African Research